Utilization of Instructional Technology in English Language Teaching (ELT) based on Constructivism: A Literature Review - Sulindra, Eric; Cendra, Anastasia Nelladia; Hartani, Tuti (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
This literature review paper explores the realm of constructivism within educational environments, specifically focusing on the use of instructional technology in English Language Teaching (ELT) for higher education. The scope of instructional technology in this paper is any kinds of technological support designed to accommodate various learning opportunities for learners by providing multiple tools or means of engagement, representation, and expression in ELT. Meanwhile, Constructivism, a prominent learning approach having been used widely in educational realm, underscores learners' active participation in constructing their own knowledge through experiences and interactions with their surroundings. Constructivism emphasizes the importance of authentic tasks and meaningful contexts in fostering knowledge transfer. The roots of constructivism trace back to Vygotsky's sociocultural theory, highlighting the role of social interactions and tools in cognitive development. The paper aims to examine how instructional technology can facilitate constructivist principles in ELT, examining global trends, knowledge acquisition, and the interplay between technology and constructivist pedagogy. The paper makes use of literature review for the methodology, based on a systematic review approach to gather and analyze relevant scholarly articles, books, reports, and conference papers concerning how instructional technology is used to employ constructivism in English Language Teaching (ELT), in higher education settings. The review also dives into practical implications and recommendations for leveraging instructional technology as scaffolding for language learners to navigate their Zone of Proximal Development effectively. Eventually, the integration of instructional technology within constructivist pedagogy presents rooms for establishing dynamic and interactive learning environments. However, thoughtful attention must be given to teaching and learning strategies, teacher support, and effective synergy of technology to obtain its full potential in enhancing student learning.